Interleukin-6 Contributes to Age-Related Alteration of Cytokine Production by Macrophages - Christian R. Gomez; John Karavitis; Jessica L. Palmer; Douglas E. Faunce; Luis Ramirez; Vanessa Nomellini; Elizabeth J. Kovacs (Mediators of Inflammation)
Here, we studied in vitro cytokine production by splenic macrophages obtained from young and aged BALB/c wild type (WT) and IL-6 knockout (IL-6 KO) mice. Relative to macrophages obtained from young WT mice given lipopolysaccharide (LPS), those from aged WT mice had decreased production of proinflammatory cytokines. In contrast, when compared to macrophages from young IL-6 KO mice, LPS stimulation yielded higher levels of these cytokines by cells from aged IL-6 KO mice. Aging or IL-6 deficiency did not affected the percentage of F4/80+ macrophages, or the surface expression of Toll-like receptor 4 (TLR4) and components of the IL-6 receptor. Overall, our results indicate that IL-6 plays a role in regulating the age-related defects in macrophages through alteration of proinflammatory cytokines, adding to the complexity of IL-6-mediated impairment of immune cell function with increasing age.